The effect of capital adequacy ratio (CAR), return on asset (ROA), inflation, BI rate on troubled financing in shariah rural banks in Indonesia 2015-2019 - Claresta Octavina Ahmad; Erika Amelia; Irhamsyah Putra (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2021)
This study aims to collect empirical evidence regarding the effect of CAR, ROA, Inflation, BI Rate / BI7DRR partially and simultaneously on problematic financing at Islamic Rural Banks (BPRS) in Indonesia for the 2015-2019 period. The method in this study using Multiple Linear Regression Analysis (OLS). The results of this study are the independent variables partially have a significant effect on the NPF variable except for the CAR variable. The variables CAR, ROA, Inflation, BI Rate / BI7DRR together influence the NPF variable. This research implies that based on CAR, ROA, Inflation, BI Rate / BI7DRR which can affect problems in BPRS in Indonesia, the results of this study have previously had similarities and differences with previous studies. The equation is that the independent variables jointly influence the dependent variable, and the difference is that the CAR variable does not have an effect on problems.